Urbanization, lifestyle change, and the growing burden of non-communicable diseases in India: evidence from a community-based study in Hyderabad - Vishwanath, Mansanpally (International Journal Of Community Medicine And Public Health, 2026)
Background: Non-communicable diseases (NCDs) are an escalating public health concern in India’s rapidly urbanizing regions, with cities like Hyderabad experiencing significant increases in disease burden linked to lifestyle and socioeconomic changes. Methods: A community-based, cross-sectional study was conducted using systematic random sampling to recruit adults aged 20 and above in urban Hyderabad. Data were collected with the WHO STEPS questionnaire, direct anthropometric measurements, blood pressure monitoring, and biochemical screening for glucose and lipid profiles. Results: The study found high prevalence rates of hypertension (up to 50% in the elderly), diabetes (25–26% in the elderly), and obesity (44% in the elderly, 37% in adults), with a greater impact on women than men. Behavioral risk factors, including sedentary lifestyle, tobacco use, poor dietary diversity, and excess salt intake, were widespread, and nearly half of hypertensive and many diabetic individuals were unaware of their diagnoses. Conclusion: These findings underscore the critical need for strengthened surveillance, targeted screening, and coordinated preventive interventions to address the rising NCD epidemic in urban India.